Political Lament: Extinction, Grief, and Embodied Silence. (September 2021) - Harvie, Timothy
This article confronts the ongoing tragedy of extinction in the Anthropocene from the standpoint of grief and embodied affect. It argues that when confronted with the death of an animal other – be it in public and political settings or in personal encounters of suffering – that silent grief is an embodied form of protest to the triumphalist and anthropocentric narratives of the neoliberal petro-state. In developing an account of suffering and grief from Miguel de Unamuno the argument proceeds to account for an embodied political praxis which subverts political structures aimed at marginalizing animal-others. Finally, in dialogue with Maurice Merleau-Ponty, the article concludes with a reflection on how scholarly activities in the mode of grief might enact relational capacities with the broader animal and natural world.